К 125-летию НТУ "ХПИ". Очерки об истории научной школы исследователей зубчатых передач в университете - Устиненко, Александр Витальевич; Полищученко, И. С. (НТУ "ХПИ", 2010)
In the article history and achievements of gearings researcher's school in the National Technical university "Kharkov polytechnic institute" is described. It is told about the most outstanding scientists, workings in KHPI in this direction. The ways of its further development are displayed
Keywords: редуктор; трансмиссия; профессор; академик; кафедра Деталей машин; книга